Modern Possibilities of Endosurgical Biopsy in Children with Chronic Liver Diseases - Polina V. Khrolenko; Elena Y. Dyakonova; Andrej N. Surkov; Aleksej A. Gusev; Tat’yana A. Prudnikova; Aleksandr S. Bekin; Ekaterina A. Romanova; Elena A. Kulebina; Elena L. Tumanova; Kirill A. Kulikov; Igor’ V. Dvoryakovskij; Dina S. Rusinova (Педиатрическая фармакология)
Chronic liver diseases in children are a group of pathological conditions which varies greatly in etiopathogenetic features heterogeneity and clinical picture, tends to progress if associated with cirrhosis and decompensate hepatic functions consequently following by orthotopic transplantation. Despite the introduction of many non-invasive methods of examination, biopsy continues to be a standard in the diagnosis of histopathological changes in liver tissue. The article reflects modern ideas about the efficacy and safety of various methods of liver biopsy in children. Comparative analysis results on the informative value of hepatobioptates obtained by various puncture techniques are provided.